2018
DOI: 10.18203/2320-6012.ijrms20184910
|View full text |Cite
|
Sign up to set email alerts
|

Role of biochemical markers in the prediction of osteopenia and osteoporosis in men and women of Sikkim, India

Abstract: Background: Osteoporosis being a silently progressing disease, the real challenge is to identify the individual at high risk of osteoporosis. Many bone turnover marker have been associated with bone loss even before occurrence of any changes in bone structure. Therefore, this study was aim to evaluate the predictive value of bone turnover marker by correlating with low bone density.Methods: This was a case control study conducted in Sikkim Manipal Institute of Medical Sciences, India. A total of 300 subjects (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A study in Sikkim proposed NTX and urinary HYP as markers in diagnosing osteoporosis in men whereas osteocalcin as an indicator in women. They concluded that bone turnover markers are able to predict low bone mass and will help to predict the risk of osteoporosis [75]. Abraham.…”
Section: Assessment Of Bone Turnover Markers In Osteoporosis In Indiamentioning
confidence: 99%
“…A study in Sikkim proposed NTX and urinary HYP as markers in diagnosing osteoporosis in men whereas osteocalcin as an indicator in women. They concluded that bone turnover markers are able to predict low bone mass and will help to predict the risk of osteoporosis [75]. Abraham.…”
Section: Assessment Of Bone Turnover Markers In Osteoporosis In Indiamentioning
confidence: 99%